A case-control study to evaluate quality of life w.s.r. to brahmamuhurta jagarana - Punit Chaturvedi; Durgawati Devi (Wolters Kluwer Medknow Publications, 2021)
Introduction: Now a days, the world's population is facing a lot more psychological problems than physical suffering. "Quality of life" refers to a subjective evaluation which is embedded in a cultural, social, and environmental context. There is a strong relationship between brahma muhurta jagarana and healthy life. This concept needs to be elaborated and explained from the Ayurveda point of view as well as justified with modern views for which this study has been planned. Materials and Methods: Six hundred volunteers were divided into two equal groups having 300 volunteers who had been waking up in brahma muhurta and other 300 volunteers who had not been waking up in the brahma muhurta. The World Health Organization quality of life-BREF was analyzed and compared in both groups. Results: Quality of life, satisfy with health, enjoy in life, able to concentrate, enough energy, satisfied with sleep, and negative feeling have significant better result (P < 0.05) in brahma muhurta jagarana groups as compared to non brahma muhurta jagarana group. Conclusion: Brahma muhurta jagarana is an important part of dinacharya to be adopted to improve the quality of life.